Problems typical of the business environment in Armenia (Using the example of the agricultural sector) - Kyuregyan, Arpine (Edelweiss Applied Science and Technology, 2025)
The business environment is the main guarantor of the economic and social stability of each country. Its development makes it possible to mitigate the economic and social difficulties characteristic of countries with economies in transition, creating stable conditions for further economic growth. Therefore, the development of the business environment affects the improvement of the quality of life in this country. The improvement of the business environment is primarily due to the processes taking place in the economy, the effective management of which contributes to increased business activity and economic development. At the same time, it is necessary to develop management mechanisms that affect the business environment, which, in turn, can lead to an increase in the number of business entities, the introduction of effective economic levers, and the formation of an effective state-business platform. As a tool for managing the business environment, the concept of a business environment administration system is discussed in the article. To increase business activity in the agricultural sector of Armenia, the article estimates the relationship between GDP, food exports, and tax burden using the least squares method and based on statistical data. The results of the model show that food exports have a positive impact on GDP; however, the tax burden has a negative impact. Therefore, this area has many problems associated with the insufficient development of state support mechanisms. The article proposes implementing targeted measures that will form a new platform for effective cooperation between the state, business, and civil society.